PELAKSANAAN HAK KEKAYAAN INTELEKTUAL DALAM KERANGKA PEMBANGUNAN BUDAYA HUKUM (DISKURSUS FILOSOFIS KEBERADAAN HAK KEKAYAAN INTELEKTUAL DI INDONESIA) - Roni Sahindra (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2022)
The basic assumption is that IPR protection is still considered foreign according to Indonesian culture. Thus, it is necessary to have a deep understanding of the philosophical basis and historical development of IPR protection as a medium for the Government to formulate policies that are in accordance with Indonesia's national development interests. The research method is normative juridical which is qualitative in nature with the main source of secondary data being carried out in this study, with a descriptive purpose. Through this research, it is concluded that until now IPR protection is needed in Indonesia in order to improve people's welfare. This is due to the fact that the need for IPR protection is a basic human trait based on the desire to gain respect, a decent living and independence in the economy. However, various policy adjustments are needed in the economic, social and cultural fields, in order to increase the effectiveness and efficiency of IPR protection in Indonesia. The reason for this view is that there is an allegation that the problem of poverty and the social and cultural conditions of the community have a very large influence on the acceptability and quality level of law enforcement